2015
DOI: 10.3389/fmicb.2015.00879
|View full text |Cite
|
Sign up to set email alerts
|

Fe biomineralization mirrors individual metabolic activity in a nitrate-dependent Fe(II)-oxidizer

Abstract: Microbial biomineralization sometimes leads to periplasmic encrustation, which is predicted to enhance microorganism preservation in the fossil record. Mineral precipitation within the periplasm is, however, thought to induce death, as a result of permeability loss preventing nutrient and waste transit across the cell wall. This hypothesis had, however, never been investigated down to the single cell level. Here, we cultured the nitrate reducing Fe(II) oxidizing bacteria Acidovorax sp. strain BoFeN1 that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 67 publications
4
47
0
Order By: Relevance
“…While some Fe(II)-oxidizing bacteria such as photoferrotrophs and the autotrophic Culture KS have developed strategies for avoiding cell encrustation by Fe(III) minerals (Hegler et al, 2010), no such strategies have been demonstrated by chemodenitrifying bacteria (Schaedler et al, 2009;Klueglein et al, 2014). Cell encrustation inhibits respiratory complexes and other periplasmic sites which leads to decreased nitrate-dependent Fe(II) oxidation (Carlson et al, 2013) and eventually results in cell death (though not always for all community members, e.g., Miot et al, 2015). (Kumaraswamy et al, 2006) and Desulfitobacterium frappieri (Shelobolina et al, 2003).…”
Section: Mechanisms Of Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…While some Fe(II)-oxidizing bacteria such as photoferrotrophs and the autotrophic Culture KS have developed strategies for avoiding cell encrustation by Fe(III) minerals (Hegler et al, 2010), no such strategies have been demonstrated by chemodenitrifying bacteria (Schaedler et al, 2009;Klueglein et al, 2014). Cell encrustation inhibits respiratory complexes and other periplasmic sites which leads to decreased nitrate-dependent Fe(II) oxidation (Carlson et al, 2013) and eventually results in cell death (though not always for all community members, e.g., Miot et al, 2015). (Kumaraswamy et al, 2006) and Desulfitobacterium frappieri (Shelobolina et al, 2003).…”
Section: Mechanisms Of Oxidationmentioning
confidence: 99%
“…For many chemodenitrifiers, precipitation occurs in the periplasm, as shells which completely enclose the cell, or in extracellular globules or as Fe filaments on extracellular polymeric substances (EPS) (Kappler et al, 2005b;Miot et al, 2009b;Schaedler et al, 2009;Schmid et al, 2014). The extent of encrustation increasingly limits the metabolic capabilities of these bacteria until encrustation is so severe that they are killed (Miot et al, 2015). The extent to which encrustation is an artefact caused by high Fe(II) concentrations in lab conditions is unclear, but such structures have been observed in the environment .…”
Section: Fe(ii) Sources and Fe(iii) Minerologymentioning
confidence: 99%
“…Phenotypic heterogeneity helps microbial populations (Ackermann, 2015) to adapt to fluctuating environmental conditions (Balaban et al, 2004;Kussell and Leibler, 2005;Acar et al, 2008;Beaumont et al, 2009;Ratcliff and Denison, 2010;Arnoldini et al, 2014;Schreiber et al, 2016), aids in the division of labour within isogenic cell populations (Ackermann et al, 2008) and can result from negative frequency-dependent interactions in mixed resource environments (Healey et al, 2016). Multiple studies on phenotypic heterogeneity have been conducted with microbial model strains, while only a few studies have investigated environmental isolates (Ziv et al, 2013;Holland et al, 2014;New et al, 2014;Miot et al, 2015;Guantes et al, 2016) or natural microbial populations Zimmermann et al, 2015;Sheik et al, 2016). Thus, there remains a knowledge gap as to how phenotypic heterogeneity is controlled in environmental bacteria without long laboratory culture history and in natural microbial populations.…”
Section: Introductionmentioning
confidence: 99%
“…This process would not affect, however, the most soluble cations (e.g., Mg, Mn, Zn, Co, Ni; Table S1), which require significantly higher pH conditions to precipitate (Sánchez-España & Yusta, 2015). Miot et al (2015) have recently shown that bacterial cells can still maintain a significant degree of carbon assimilation and metabolic activity even with an important level of Fe-mineral encrustation. Using a combination of electron microscopy and nanoSIMS, these authors found that there was a maximum extent of periplasmic mineral encrustation above which cells of the nitrate-reducing, Fe(II)-oxidizing bacteria Acidovorax sp.…”
Section: Silica Adsorptionmentioning
confidence: 99%